HOW HEALTH SERVICE? PERSPECTIVE OF MATERNAL IN EAST NUSA TENGGARA PROVINCE, INDONESIA - Seran, Agustina Abuk; Antaria, Myrtati Dyah; Haksama, Setya; Setijaningrum, Ema (International Journal of Psychosocial Rehabilitation, 2020)
The utilization of maternal health services in Indonesia is still low, especially in rural areas. This condition also occurs in the community in the work area of the Babulu Selatan Community Health Center in Malacca Regency. The community is still giving birth at home. This study will examine access to maternal health services from the perspective of the public as health care users who are less noticed. This study was designed in a descriptive qualitative manner, collecting data with in-depth interviews, Focus Group Discussion (FGD) and observations in the field. Research location in Malacca District in February-April 2019. The results illustrate the accessibility of maternal health services in general, the community believes that it is still lacking. Physical access is difficult to reach due to poor infrastructure and facilities. Also, social access is felt to be lacking because health providers are not friendly and careless, people believe in traditional birth attendants and cultural practices. The conclusion of this research, in general, is that the community still feels barriers to physical access and social access. For this reason, it is necessary to recommend the local government to improve physical access and health services to make efforts to increase public awareness to utilize maternal health services.